Uniportal video-assisted thoracic surgery left superior segmentectomy with systematic lymphadenectomy in the semiprone position - Lin, Zongwu; Xi, Junjie; Xu, Songtao; Wang, Qun (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
A 63-year-old male was referred to our hospital with two existing lesions in bilateral lungs. Computed tomography (CT) showed a 15-mm ground-glass opacity (GGO) in the superior segment of left lower lung (S6) and a 5-mm GGO in the center of the right upper lobe. The preoperative clinical diagnosis was stage I primary lung cancer for the left lesion while the right lesion needed follow-up. Uniportal video-assisted thoracic surgery (VATS) left superior segmentectomy in the semiprone position was performed in this case and the right upper lobe was kept untouched. Frozen section examination confirmed the diagnosis of lung adenocarcinoma, and systematic lymphadenectomy with non-grasping en bloc dissection technique was then performed. A chest tube was placed at the posterior part of the incision through the dorsal thoracic cavity to the apex. The postoperative pathologic diagnosis was minimally invasive adenocarcinoma, staged T1aN0M0.